Pengaruh Jumlah Uang Beredar, Inflasi, dan Suku Bunga BI Rate Terhadap Jakarta Islamic Index (JII) Periode Tahun 2020 – 2022 - Widiastuti, Rini; Prastiwi, Iin Emy; Sumadi, Sumadi (Jurnal Ilmiah Ekonomi Islam, 2024)
This research was conducted to analyze the effect of macroeconomic variables, especially the amount of money in circulation, inflation, and the BI Rate on the Jakarta Islamic Index (JII) in the period 2020 – 2022. The data in this study were collected from time series data from the month January 2020 to December 2022 which is carried out by observing the closing price of the stock price index every month. Data analysis used the classical assumption test with the data analysis method using multiple linear regression methods, in addition to that, the F test, t test, and the coefficient of determination were also carried out. The results of the study show that the money supply variable (M2) partially has no significant effect on the Jakarta Islamic Index with a tcount of 1.901 and a ttable of 2.03693. The inflation variable partially has a significant effect on the Jakarta Islamic Index with a tcount of 2.322 and a ttable of 2.03693. Meanwhile, the BI interest rate variable partially has no significant effect on the Jakarta Islamic Index with a tcount of -0.951 and a ttable of 2.03693.